A blow up result in the Cauchy problem for a semi-linear accretive wave equation (Global Journal of Science Frontier Research, 2011)
We investigate the blow up of the semi -linear wave equation given by u tt -Δu = |u t | p-1 u t , and prove that for a given time T>0, there exist always initial data with sufficiently negative initial energy for which the solution blows up in time ≤T.
Keywords: Wave equation; Negative initial energy; blow up; finite time